Computer Usage Behavior Relationship Against Refraction Status in Students of the Faculty of Medicine, University of Muhammadiyah Semarang - Kurniati, Ika Dyah; Martiningsih, Wahju Ratna; Swasty (Ahmad Dahlan Medical Journal, 2023)
During the 2019 COVID pandemic, the learning process was carried out online so that the level of computer usage was higher every day. Physical disorders that often occur due to computer use in the eyes, include refractive errors, one of which is myopia. The purpose of this study was to determine the relationship between visual distance, sitting position and computer screen brightness on refractive status in students of the Faculty of Medicine, University of Muhammadiyah Semarang. This research is an analytic observation research by design cross-sectional. The sample for this study was students from class 2019 – 2021 at the Faculty of Medicine, Muhammadiyah University, Semarang. Sampling technique using simple random sampling which selects objects at random. Researchers used the questionnaire method where the questionnaire contained written questions that had been validated. The data obtained were analyzed using the chi-square test. The number of respondents to this study was 74 students. The distance from the eye to the screen of the most respondents is close distance as many as 40 people (54.1%), The position of the most respondents when using a laptop is bending as many as 50 people (67.6%), The brightness of the laptop screen used by most respondents uses optimal brightness as much as 73 people (98.6%). Respondents who experienced an increase in myopia were 24 (32.5%). The results of this study showed that there was no relationship between distance (p 0.456), sitting position (p 0.690) and screen brightness (p 0.485) on refractive status, because both respondents the distance, position and lighting are appropriate or not, all show almost the same percentage to experience an increase in myopia.